Vibroacoustic Prediction of a High-Temperature Superconducting Field-Modulation Double-Stator Machine with Stationary Seal - Yubin Wang (Energies, 2018)
This paper predicted the vibroacoustic regularity of a high temperature superconducting (HTS) field-modulation double-stator (HTS-FMDS) machine with stationary seal for low-speed and direct-drive applications. The originality of this paper lies in that the spatial order and angular velocity of electromagnetic-force density of the HTS-FMDS machine were derived by using the analytical method. Moreover, the validity of the analytical solutions was verified by the finite element analysis (FEA) results. Then, the modal shapes and frequencies of the outer stator were obtained by using multiphysics coupling simulation. By transferring the electromagnetic force to the stator structural model, the regularity of electromagnetic vibration and noise of the HTS-FMDS machine were revealed.